Automation and Technological Change hearings before the United States Joint Committee on the Economic Report, Subcommittee on Economic Stabilization, Eighty-Fourth Congress, first session, on Oct. 14, 15, 17, 18, 24-28, 1955. - United States. Congress. Joint Committee on the Economic Report. Subcommittee on Economic Stabilization (Washington U.S. G.P.O., 1955)
Examines industrial and employment impact of automation.
Keywords: Automation -- Economic aspects -- United States; Automation -- Social aspects -- United States; Industrial productivity -- United States; Technological innovations -- United States